Descriptive analysis and trends of pre-degree theses in Peruvian faculties of dentistry - Moromi Nakata, Hilda (2022)
Introduction: The analysis of dentistry thesis in Peru, provides valuable information to optimize efforts related to solving oral health problems. Objective: To analyze undergraduate dental theses from Peruvian universities during 2015-2019. Method: Descriptive, associative and quantitative study. 1389 theses from 14 public and private universities were analyzed. The variables: university name and type, number of authors, access to full text, academic-professional areas, type of research and orientation to prevalent diseases in the oral cavity, year and origin region. Results: Of the total number of theses, access to the full text was obtained in 66.5%, an 87.7% had only one author and the 66.7% was descriptive research. The most frequent academic-professional areas of study were: Pediatric and Social Stomatology with 27% and Surgical Medical Stomatology with 20.4%. The orientation to dental caries was 19.2%, to occlusion diseases 11.4% and to periodontal disease 8.1%. Discussion: The results were similar to other authors, with few studies related to the prevalent diseases. It is suggested that the faculties of Dentistry reorient research primarily to the needs and policies of oral health, to achieve a better contribution of academia to society.